Obtenção de polpa de manga (Mangifera indica L.) em pó pelo processo em spray-dryer - Lara Júnior, Jovan Marques (2017)
The transformation of fruits into poder, specially the mango, comes against the needing of improving the yield of these fruits and also add some value to the product. This work aims to obtain mango’s pulp in poder using the spray-dryer process. The variety of mango tommy atkins was used as raw material. The work was divided into: microscopic evaluation, sorption isotherms and pulping characteristics of the pulp powder at different levels of maltodextrin; experimental design, where the yield, moisture, coordinate b* and ascorbic acid content were evaluated as variables; characterization of the whole pulp and the pulp powder with 30 % maltodextrin, where moisture, water activity, soluble solids content, ph, titratable total acidity, ascorbic acid, color (L*, a* and b*), total carotenoids, reducing and total sugars, solubility and hygroscopicity were evaluated; and study the physical-chemical stability of the pulp powder with 30% maltodextrin. When evaluating the particles microscopically it was observed that the control samples and the samples with 10 % of maltodextrin presented bridges interconnecting the particles. The particles in the 20 and 30 % maltodextrin samples presented more rounded, heterogenic but clustered forms. For the isotherms at the temperatures and concentrations evaluated, the gab model more accurately described the sorption isotherms of the powdered mango pulp, presenting R2 values close to 1 and errors less than 10 %. When checking the values of the flow indices of the evaluated samples, it was observed that they presented a cohesive behavior. The experimental design showed that the best parameter to be used in mango drying was 30 % maltodextrin and temperature at 130 °C. In the characterization, the evaluated parameters, with the exception of pH, presented significant differences between the mango pulp and the mango pulp powder at a 95 % confidence level. The experimental design showed that the best parameter to be used in the mango’s drying was with 30 % of maltodextrin and temperature of 130 ºC. In the characterization, the evaluated parameters, with the exception of ph, presented significant differences between the mango pulp and the mango pulp powder at a 95 % confidence level. A reduction of 72.63 % of the ascorbic acid content and a significant reduction (p ≤ 0.05) of the b * coordinate, in the colorimetric test, in the order of 56.4 % between the whole pulp and its atomized powder . The spray-drying process was an efficient method in drying mango’s pulp with the use of maltodextrin as a drying aid. The pulp of mango powder was stable during 90 days of storage in laminated and polyethylene packages.